PENGARUH FASILITAS BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X MATA PELAJARAN EKONOMI DI SMA NEGERI 11 KOTA JAMBI - Kasiono, Anuar (Universitas Batanghari Jambi, 2018)
AbstractThis study aims to determine the description of respondents and the influence of learning facilities and learning motivation on the learning outcomes of students of class X economic subjects in SMA Negeri 11 Kota Jambi. Based on the data analysis on the results of research that there is a significant influence between learning facilities and learning motivation in the learning outcomes of students of class X economic subjects in SMA Negeri 11 Kota Jambi. With result of model summary R = 0, 138 and R Square = 0,119. In ANOVA, the value of F = 11.035 with α (sig) = 0.003. Because α (Sig) <0.05, then regression can be used to predict learning facilities and learning motivation at 95% confidence level. Based on the value of B constant for X, we can make a regression equation that is Y = a + X1 + X2 = 82,440 + 0,177 + 0,280. And, for t arithmetic X1 = 4.002, and t arithmetic X2 = 11.378 then t arithmetic> t table. That is, t test results indicate that learning facilities and motivation to learn have a positive and significant effect on learning outcomes (Y) students class X economic subjects in SMA Negeri 11 Kota Jambi.Keyword : Learning Facilities, Learning Motivation, Learning Outcomes.